2021
DOI: 10.3390/microorganisms9030646
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Prediction and Analysis of Unusual Lantibiotic Resistance Operons in the Genus Corynebacterium

Abstract: Post-translationally modified, (methyl-)lanthionine-containing peptides are produced by several Gram-positive bacteria. These so-called lantibiotics have potent activity against various bacterial pathogens including multidrug-resistant strains and are thus discussed as alternatives to antibiotics. Several naturally occurring mechanisms of resistance against lantibiotics have been described for bacteria, including cell envelope modifications, ABC-transporters, lipoproteins and peptidases. Corynebacterium specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
6
1
1
Order By: Relevance
“…Although previous studies reported C. glutamicum to be resistant to up to 40 µg/ml of nisin [ 46 ], our own results suggest that growth of C. glutamicum is completely inhibited by ~ 1 µg/ml of nisin [ 47 , 48 ]. To corroborate these results and to determine the nisin concentration that is required for formation of pores in the membrane of C. glutamicum , we devised a biosensor expressing the pH-dependent fluorescent protein pHluorin2 [ 49 ] in a similar fashion as described recently for L. monocytogenes [ 50 ].…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…Although previous studies reported C. glutamicum to be resistant to up to 40 µg/ml of nisin [ 46 ], our own results suggest that growth of C. glutamicum is completely inhibited by ~ 1 µg/ml of nisin [ 47 , 48 ]. To corroborate these results and to determine the nisin concentration that is required for formation of pores in the membrane of C. glutamicum , we devised a biosensor expressing the pH-dependent fluorescent protein pHluorin2 [ 49 ] in a similar fashion as described recently for L. monocytogenes [ 50 ].…”
Section: Resultscontrasting
confidence: 70%
“…1 A). This indicates that recombinant production of active nisin is not possible using C. glutamicum as the product not only inhibits growth [ 47 , 48 ] but kills producer cells at low concentrations.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In silico analyses using the web-based tool BAGEL4 revealed several, yet undescribed bacteriocin gene clusters (BGC) in the genus Corynebacterium (8). In this study, we closely examined one of the predicted BGCs in the genome of C. lactis RW2-5 isolated from raw cow’s milk and found an identical cluster in the strain C. lactis RW3-42 upon sequencing of the locus (30).…”
Section: Resultsmentioning
confidence: 99%
“…Actinobacteria. Nevertheless, several studies suggest the widespread occurrence of bacteriocin gene clusters (BGCs) in non-LAB species, including the genus Corynebacterium (7)(8)(9)(10). Species of this genus are wide-spread in nature, make up one of the largest groups of bacteria in the human and animal skin microbiome and are also present in food products including raw milk or cheese (11)(12)(13).…”
mentioning
confidence: 99%
“…Auch hier profi tiert die Forschung der letzten Jahre jedoch von den oben beschriebenen, neuen Methoden zur Identifi zierung neuartiger Bacteriocine. Durch in silico-Analysen öffentlich zugänglicher Corynebacte rium-Genome konnten wir zeigen, dass mindestens ein Viertel der analysierten Spezies ein oder mehrere Gencluster für die Biosynthese von Bacteriocinen besitzen [7]. In den vorhergesagten Genclustern konnten indikative Gene für alle bislang beschriebenen Bacteriocin-Klassen gefunden werden, was auf ein ähnlich diversifi ziertes Vorkommen schließen lässt, wie es auch bei den Milchsäurebakterien der Fall ist.…”
Section: Bacteriocine Von Corynebakterienunclassified